The Renewal of Islam in Minangkabau’s Community from Paderi to Young Generation: A Perspective Study on History and Islamic Characteristics - Kasmuri Selamat (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
This paper discusses the renewal of Islam by Paderi in Minangkabau’s community, west Sumatera, Indonesia. Seventy years after the Paderi movement stopped because young scholars known as the Youth Generation (YG) continued Dutch colonial pressure with original models and characteristics. To delve into this problem, a historical research method was required to test and analyze the vital records and relics of the yesteryear. This research is qualitative. The research and discussion found: first, the reform in Islam consisted of 2 indicators, namely (1) the returns of Islamic purity to the guidance of the Qur'an and Hadiths, and (2) modernization as a representation of the youth movement. Second, the violence by the Paderi was inappropriate if related to Minangkabau’s cultures which were tolerant and familial. The first Islamization process in Minangkabau was also never penetrated by a power of politics such as war. Third, the conflict had triggered a vivacious and dynamic religious discourse. We could see this from many meetings and debates held both during the Paderi and during Youth Generation. Besides, various schools had appeared, publishing books and magazines from each generation to socialize and make a struggle for religious understanding.